Minimum Wages and Informality - Ellora Derenoncourt; Francois Gerard; Lorenzo Lagos; Claire Montialoux (Institute of Labor Economics (IZA), 2025)
How do minimum wages affect informality? We study the near-doubling of the real minimum wage from 2000 to 2009 in Brazil, where 46% of the workforce is informal. Using labor force surveys covering the informal sector, we show the minimum wage exhibits near full passthrough to informal employees working in formal firms, about half of all informal employees. The formal-to-informal reallocation elasticity with respect to the formal wage is small: -0.28. Our findings illustrate how minimum wages can positively affect living standards for workers thought beyond the reach of labor law, a sizable share of the workforce in developing economies.
Keywords: J23; J46; J88; 330; minimum wages; informality; inequality